Gut microbe and hepatic macrophage polarization in non-alcoholic fatty liver disease - Chen, Yao; Gan, Yumeng; Zhong, Huijie; Liu, Yincong; Huang, Jingdi; Wang, Wenxue; Geng, Jiawei (Frontiers in Microbiology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a common chronic hepatic disorder with the potential to progress to hepatic fibrosis, hepatic cirrhosis, and even hepatocellular carcinoma. Activation of hepatic macrophages, important innate immune cells predominantly composed of Kupffer cells, plays a pivotal role in NAFLD initiation and progression. Recent findings have underscored the regulatory role of microbes in both local and distal immune responses, including in the liver, emphasizing their contribution to NAFLD initiation and progression. Key studies have further revealed that gut microbes can penetrate the intestinal mucosa and translocate to the liver, thereby directly influencing hepatic macrophage polarization and NAFLD progression. In this review, we discuss recent evidence regarding the translocation of intestinal microbes into the liver, as well as their impact on hepatic macrophage polarization and associated cellular and molecular signaling pathways. Additionally, we summarize the potential mechanisms by which translocated microbes may activate hepatic macrophages and accelerate NAFLD progression.